2019
DOI: 10.5004/dwt.2019.23849
|View full text |Cite
|
Sign up to set email alerts
|

Research on the expansion mechanism of hydraulic fracture branching induced by weak bedding shear slip

Abstract: a b s t r a c tBedding fracture is the main rock mass of the tight reservoir; the main method for the formation of complex fractures of dense rock is to activate weak bedding to induce the branch extension of hydraulic fracture. Based on fracture mechanics, this paper established the mechanical model of coupled extension with weak bedding when the hydraulic fracture is close to the weak bedding process, adopted the numerical analysis method, based on the equivalent principle of coupling, through unit compilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Zheng et al (2019) and Zheng et al (2022) analyzed the evolution of normal stress and shear stress on the bedding plane when the hydraulic fracture approached through the block distinct element method, and identified the discontinuous deformation (slip or shear failure) at the fracture tip as the main reason why the hydraulic fracture could not cross the bedding. Wang et al (2019) also showed that the increase of shear stress on the bedding plane and the passivation of fracture tip affect the penetration of hydraulic fractures. Tan et al (2021) proposed the notion of transition zone in the layered formation and investigated the effects of multiple influencing factors on hydraulic fracture vertical propagation behavior based on XFEM-based CZM method.…”
Section: Introductionmentioning
confidence: 98%
“…Zheng et al (2019) and Zheng et al (2022) analyzed the evolution of normal stress and shear stress on the bedding plane when the hydraulic fracture approached through the block distinct element method, and identified the discontinuous deformation (slip or shear failure) at the fracture tip as the main reason why the hydraulic fracture could not cross the bedding. Wang et al (2019) also showed that the increase of shear stress on the bedding plane and the passivation of fracture tip affect the penetration of hydraulic fractures. Tan et al (2021) proposed the notion of transition zone in the layered formation and investigated the effects of multiple influencing factors on hydraulic fracture vertical propagation behavior based on XFEM-based CZM method.…”
Section: Introductionmentioning
confidence: 98%